Exploring the Effectiveness of Using Big Books in Teaching Primary English in Malaysian Classrooms (Malaysian Journal of Learning and Instruction, 2008)
There are many benefits of using stories for language and literacy development particularly in the areas of vocabulary (Cameron, 2001; Elley, 1989; Penno, Wilkinson & Moore 2002; Hargrave & Senechal, 2000) and reading comprehension. Yet, much is still unknown in second language (L2) contexts. This paper investigates the use of Big Books in primary English in Malaysia where English is taught as an official second language. It draws on transcript data from one teacher from one primary school to illustrate how students’ active participation and interest in language learning emerged as the teacher introduced Big Books instead of the textbook. Our data shows that practice with Big Books changes the interaction patterns and learning opportunities. Students were actively involved and they contributed to the discussions and made spontaneous comments about the stories. Most importantly, the teacher’s elicitation skill is essential in enhancing students’ learning. The Ministry of Education’s hopes to provide more active engagement and to increase students’ interests and motivation through stories were achieved.